Plastid Genome Comparative and Phylogenetic Analyses of the Key Genera in Fagaceae: Highlighting the Effect of Codon Composition Bias in Phylogenetic Inference - Yang, Yanci; Zhu, Juan; Feng, Li; Zhou, Tao; Bai, Guoqing; Yang, Jia; Zhao, Guifang (Frontiers in Plant Science, 2018)
Fagaceae is one of the largest and economically important taxa within Fagales. Considering the incongruence among inferences from plastid and nuclear genes in the previous Fagaceae phylogeny studies, we assess the performance of plastid phylogenomics in this complex family. We sequenced and assembled four complete plastid genomes (Fagus engleriana, Quercus spinosa, Quercus aquifolioides and Quercus glauca) using reference-guided assembly approach. All of the other twelve published plastid genomes in Fagaceae were retrieved for genomic analyses (including repeats, sequence divergence and codon usage) and phylogenetic inference. The genomic analyses reveal that plastid genomes in Fagaceae are conserved. Comparing the phylogenetic relationships of the key genera in Fagaceae inferred from different codon positions and gene function datasets, we found that the first two codon sites dataset recovered nearly all relationships and received high support. Thus, the result suggested that codon composition bias had great influence on Fagaceae phylogenetic inference. Our study not only provides basic understanding of Fagaceae plastid genomes, but also illuminates the effectiveness of plastid phylogenomics in resolving relationships of this intractable family.